Novel anti-seepage mortar for backwater wall surface and construction process of novel anti-seepage mortar

By improving the composition and preparation process of the new anti-seepage mortar on the backwater wall, combined with the magnetic field treatment of iron powder by magnets and the injection of inorganic salt sealant and epoxy resin, the problems of insufficient anti-seepage pressure, limited mechanical properties and complex construction in the existing technology are solved, significantly improving the anti-seepage performance and construction performance, and enhancing durability and service performance.

CN119774958AActive Publication Date: 2025-04-08BAODING YUJIAN WATERPROOF TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510035834.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-08
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing anti-seepage mortar on the backwater wall has shortcomings in compressive strength, anti-seepage performance and construction convenience, especially in high water pressure and complex environments, it is difficult to meet the long-term and stable waterproofing needs.

Method used

By improving the composition and preparation process of the new anti-seepage mortar of backwater wall, it includes the use of silicate cement, fast hard sulfaluminate cement, quartz sand, corundum powder, anti-seepage modified fiber, redispersible glue powder, water reducing agent, water repellent, water repellent, N-benzylhexadecanoamide, 4-iodophenylacetylene trimethylsilane, iron powder, retarder and acrylic emulsion, and the magnetic field treatment and guidance of the iron powder by magnets is used to form a predetermined membrane channel. At the same time, an inorganic salt sealant and epoxy resin are injected into the mortar through the membrane channel to enhance the anti-seepage performance.

Benefits of technology

The anti-seepage and construction performance of the new mortar on the backwater wall is significantly improved, the durability and service performance of the mortar is enhanced, and the penetration and accumulation of moisture can be effectively prevented, and the mechanical properties of the mortar are improved, and the construction process is simplified, which reduces the construction cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774958A_ABST
    Figure CN119774958A_ABST
Patent Text Reader

Abstract

The invention discloses novel anti-seepage mortar for a backwater wall surface and a construction technology of the novel anti-seepage mortar, and relates to the technical field of building materials. The anti-seepage concrete is prepared from the following components in parts by weight: 40 to 50 parts of Portland cement, 10 to 15 parts of quick-hardening sulphoaluminate cement, 280 to 320 parts of quartz sand, 22 to 26 parts of emery powder, 10 to 12 parts of anti-seepage modified fiber, 0.3 to 0.5 part of redispersible rubber powder, 2.8 to 3.0 parts of a water reducing agent, 0.5 to 0.7 part of a water repellent, 4 to 6 parts of N-benzyl hexadecanamide, 2 to 4 parts of 4-iodophenylacetylene trimethylsilane, 15 to 25 parts of iron powder, 0.5 to 1.5 parts of a retarder and 2.5 to 5 parts of acrylic emulsion. By improving the components and the preparation process of the novel seepage-proofing mortar for the backwater wall surface, the seepage-proofing performance and the construction performance of the novel seepage-proofing mortar for the backwater wall surface are improved, and the durability and the use performance of the mortar are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a new type of anti-seepage mortar for backwater walls and a construction process thereof. Background Art

[0002] Backwater wall anti-seepage mortar is a waterproof mortar material specially used for backwater surfaces. It is mainly refined from special cement, quartz sand, active microcrystals and other functional additives, and has the characteristics of excellent waterproof performance, good adhesion, high compressive strength and durability.

[0003] With the continuous development of the construction industry, the requirements for the waterproof performance of building materials are increasing. As a waterproof mortar material specially used for the back water surface, the performance of the back water wall anti-seepage mortar directly affects the service life and safety of the building. At present, although the back water wall anti-seepage mortar on the market can meet the waterproofing needs to a certain extent, it still has shortcomings in terms of compressive strength, anti-seepage performance and construction convenience.

[0004] For example, the Chinese patent with application number CN202311234030.4, interface mortar for anti-corrosion coating and preparation method thereof, the invention relates to an interface mortar for anti-corrosion coating and a preparation method thereof, belonging to the field of building materials technology. The interface mortar comprises, by weight, 100 parts of cement, 260-330 parts of quartz sand, 20-28 parts of corundum powder, 8-13 parts of anti-seepage modified fibers, 15-22 parts of redispersible rubber powder, 2.6-3.2 parts of water reducer and 0.5-0.7 parts of defoamer. The anti-seepage modified fibers are not easy to agglomerate, have good hydrophilicity and are easily dispersed in the mortar. They can react with the polyacrylate segments in the redispersible rubber powder to strengthen the strengthening effect of the fibers. The positive charge on the surface of the anti-seepage modified fibers has an electrostatic adsorption effect on negatively charged cement particles. The nitrogen-oxygen structure has a chelating effect on the corundum powder, forming a powder enrichment layer near the surface of the fibers. After hydration, a dense hydration layer is formed to wrap the fiber structure. The structure is interlaced and entangled in the mortar to form a water-blocking barrier, which lengthens the water penetration channel and has better anti-seepage ability.

[0005] Although the above scheme has improved the anti-seepage ability to a certain extent, it still has problems such as insufficient anti-seepage pressure, limited mechanical properties and complicated construction process. Especially under harsh conditions such as high water pressure and complex environment, it is difficult to meet long-term and stable waterproofing needs. Summary of the invention

[0006] The embodiments of the present application solve the problems of insufficient anti-seepage pressure, insufficient mechanical properties and complicated construction process existing in the prior art by providing a new type of anti-seepage mortar for backwater walls and its construction process. By improving the composition and preparation process of the new type of anti-seepage mortar for backwater walls, the anti-seepage performance and construction performance are improved, and the durability and performance of the mortar are enhanced.

[0007] The embodiment of the present application provides a new type of anti-seepage mortar for backwater wall, which comprises, by weight: 40-50 parts of silicate cement, 10-15 parts of fast-hardening sulphoaluminate cement, 280-320 parts of quartz sand, 22-26 parts of corundum powder, 10-12 parts of anti-seepage modified fiber, 0.3-0.5 parts of redispersible rubber powder, 2.8-3.0 parts of water reducer, 0.5-0.7 parts of water repellent, 4-6 parts of N-benzyl hexadecanoic acid amide, 2-4 parts of 4-iodophenylethynyltrimethylsilane, 15-25 parts of iron powder, 0.5-1.5 parts of retarder, and 2.5-5 parts of acrylic emulsion; The iron powder is pretreated, and the specific steps are: Step A1, 15-25 parts by weight of iron powder and 2.5-5 parts of acrylic emulsion are mixed uniformly in a blender at a stirring speed of 60-100 rpm for 5-10 minutes, so that the acrylic emulsion is uniformly coated on the surface of the iron powder; Wherein, the particle size of the iron powder is 100-200 mesh; Step A2, adding 0.5-1.5 parts of retarder to the mixed iron powder and acrylic emulsion and mixing evenly to form an iron powder mixture; Step A3: Place the treated iron powder mixture in a drying oven, control the temperature at 40-60°C, and dry for 2-4 hours to ensure that the film-forming components form a stable film layer on the surface of the iron powder to obtain film-forming iron powder.

[0008] Furthermore, the preparation of the new type of anti-seepage mortar for backwater wall comprises the following specific steps: Step B1, 40-50 parts of silicate cement, 10-15 parts of rapid hardening sulphoaluminate cement, 280-320 parts of quartz sand, 22-26 parts of corundum powder, 10-12 parts of anti-seepage modified fiber, 0.3-0.5 parts of redispersible rubber powder, 2.8-3.0 parts of water reducer, 0.5-0.7 parts of water repellent, 4-6 parts of N-benzyl hexadecanoic acid amide and 2-4 parts of 4-iodophenylethynyltrimethylsilane are mixed uniformly to form a base mortar; Step B2: Add film-forming iron powder to the base mortar, use a mixer to mix all components evenly at a stirring speed of 150-250 rpm, add water during the stirring process, and adjust the consistency of the slurry to 45-55 mm to obtain a new type of anti-seepage mortar for back-water wall.

[0009] Furthermore, the new anti-seepage mortar for backwater walls also includes 5-10 parts by weight of an inorganic salt plugging agent; the inorganic salt plugging agent is calcium chloride, and the concentration of the calcium chloride solution is 5%-10%.

[0010] Furthermore, the inorganic salt plugging agent solution also includes three different concentration ranges of inorganic salts: a low concentration of 1%-3%, a medium concentration of 5%-8%, and a high concentration of 10%-15%.

[0011] Furthermore, the usage ratio of the inorganic salts in different concentration ranges is: low concentration inorganic salts account for 10%-20% of the total amount of the plugging agent, medium concentration inorganic salts account for 30%-40% of the total amount of the plugging agent, and high concentration inorganic salts account for 40%-60% of the total amount of the plugging agent.

[0012] Furthermore, the new type of anti-seepage mortar for backwater wall also includes epoxy resin; the amount of epoxy resin used is 5%-20% of the total amount of the inorganic salt plugging agent.

[0013] A construction process of a new type of anti-seepage mortar for backwater wall, the specific steps are: Step C1, treating the wall surface to make it clean, free of oil stains and impurities, and setting magnets on the construction wall surface. The arrangement of the magnets is set according to the required membrane channel pattern; Step C2, applying mortar, using a plastering tool to evenly apply the mortar on the wall surface, the film-forming iron powder is attracted by the magnet during the application process to form a predetermined membrane channel; Step C3: After the application is completed, the mortar is cured to allow it to fully harden and form.

[0014] Furthermore, after the predetermined membrane channel is formed in step C2, 5-10 parts of an inorganic salt plugging agent are injected into the mortar through the membrane channel, specifically: Step C3: After the application is completed, the mortar is initially cured, the magnet is removed, and the membrane channel remains open; Inject inorganic salt plugging agent solution into the mortar through the membrane channel, with an injection pressure of 0.2-0.5MPa; Continue to cure the mortar to allow the inorganic salt plugging agent to crystallize inside the mortar, plugging the membrane channels and gaps to form a dense anti-seepage layer, and cure until the mortar is fully hardened and formed.

[0015] Furthermore, in step C3, low-concentration, medium-concentration and high-concentration inorganic salt plugging agent solutions are injected in sequence according to the dosage ratio.

[0016] Furthermore, in step C3, after the inorganic salt is completely dried, epoxy resin is injected into the pores on the surface of the mortar through the membrane channel; the injection pressure of the epoxy resin is 0.1-0.3 MPa.

[0017] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, as a ferromagnetic material, iron powder will be magnetized and generate magnetic moment in the magnetic field, thus producing directional arrangement under the action of the external magnetic field; the magnetic field generated by the magnet will attract the iron powder to move, and since the surface of the iron powder is coated with film-forming components, the film-forming substances on the iron powder will also form a path as the iron powder moves; by adjusting the magnetic field strength and direction of the magnet, the arrangement and orientation of the iron powder in the mortar can be controlled; the direction of the magnetic moment is consistent with the direction of the external magnetic field, which enables the iron powder particles to be oriented in the magnetic field; by setting magnets on the wall in advance and arranging them according to the desired membrane channel pattern, a magnetic field with a specific direction can be formed, and when the mortar is applied, the film-forming iron powder in the mortar will be attracted by this magnetic field, thereby moving in a directional manner along the direction of the magnet arrangement to form a predetermined membrane channel; Secondly, the membrane channel provides a path for the injection of inorganic salt plugging agents. Under pressure, the inorganic salt plugging agent solution can penetrate into the small gaps and capillaries inside the mortar through the membrane channel. As the water evaporates or participates in the reaction, the inorganic salt crystallizes inside the mortar to form a dense plugging layer; the inorganic salt will undergo a hydrolysis reaction in water to generate corresponding hydration products, which can fill the small gaps and capillaries inside the mortar to form a dense anti-seepage layer; after the application is completed, the mortar is initially cured to slightly harden its surface, but the interior still maintains humidity, which is conducive to the penetration and crystallization of the inorganic salt. After removing the magnet, the membrane channel formed by the iron powder remains open, providing conditions for the injection of inorganic salts; the mortar is continued to be cured, so that the inorganic salt plugging agent crystallizes inside the mortar, plugging the membrane channels and gaps to form a dense anti-seepage layer; Third, inorganic salts will undergo hydration reaction when in contact with water to generate hydration products. These hydration products can fill the pores and capillaries in the mortar, thereby improving the density of the mortar. The speed and degree of hydration reaction of inorganic salt solutions of different concentrations are different. Low-concentration solutions have strong permeability and can quickly enter the mortar; medium-concentration solutions begin to form hydration products while penetrating; high-concentration solutions form a dense plugging layer; by introducing inorganic salt solutions of different concentrations, a concentration gradient can be formed. Low-concentration inorganic salt solutions first penetrate into the mortar, providing a penetration path for subsequent medium and high-concentration inorganic salt solutions. Medium-concentration inorganic salt solutions further block pores and enhance the density of the mortar. High-concentration inorganic salt solutions form a dense plugging layer, which effectively prevents water penetration; by controlling the dosage ratio of inorganic salts of different concentrations, the performance of the plugging agent can be optimized. Low-concentration inorganic salts are used in moderate amounts to ensure permeability; medium-concentration inorganic salts are used in larger amounts to enhance the plugging effect; high-concentration inorganic salts are used in the largest amounts to form a tight plugging layer; Fourthly, epoxy resin is a high-performance polymer material with excellent adhesion and wear resistance. After the inorganic salt is completely dried, injecting epoxy resin into the pores on the mortar surface through the membrane channel can further block the pores on the mortar surface and enhance the anti-seepage performance of the mortar. After injection, the epoxy resin will penetrate into the pores on the mortar surface and form a tight bond with the inorganic salt sealant inside the mortar; as the epoxy resin solidifies, a dense polymer film will be formed, covering the surface of the mortar, effectively preventing the penetration of moisture and harmful substances; by injecting epoxy resin, the end blocking of the pores inside and on the surface of the mortar is achieved, ensuring the stability of the system materials inside the mortar; the polymer film formed after the epoxy resin is cured has good durability and chemical stability, and can protect the mortar from erosion by the external environment for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a schematic diagram of the membrane channel of Example 1 of the present invention. DETAILED DESCRIPTION

[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0020] Embodiment 1: A new type of anti-seepage mortar for backwater wall, comprising, by weight: 40-50 parts of Portland cement, 10-15 parts of fast-hardening sulphoaluminate cement, 280-320 parts of quartz sand, 22-26 parts of corundum powder, 10-12 parts of anti-seepage modified fiber, 0.3-0.5 parts of redispersible rubber powder, 2.8-3.0 parts of water reducer, 0.5-0.7 parts of water repellent, 4-6 parts of N-benzyl hexadecanoic acid amide, 2-4 parts of 4-iodophenylethynyltrimethylsilane, 15-25 parts of iron powder, 0.5-1.5 parts of retarder, 2.5-5 parts of acrylic emulsion; The iron powder is pretreated, and the specific steps are: Step A1, 15-25 parts by weight of iron powder and 2.5-5 parts of acrylic emulsion are mixed uniformly in a blender at a stirring speed of 60-100 rpm for 5-10 minutes, so that the acrylic emulsion is uniformly coated on the surface of the iron powder; Wherein, the particle size of the iron powder is 100-200 mesh; Step A2, adding 0.5-1.5 parts of retarder to the mixed iron powder and acrylic emulsion and mixing evenly to form an iron powder mixture; Step A3, placing the treated iron powder mixture in a drying oven, controlling the temperature at 40-60°C, and drying for 2-4 hours, to ensure that the film-forming components form a stable film layer on the surface of the iron powder to obtain film-forming iron powder; The preparation of the new type of anti-seepage mortar for backwater wall comprises the following specific steps: Step B1, 40-50 parts of silicate cement, 10-15 parts of rapid hardening sulphoaluminate cement, 280-320 parts of quartz sand, 22-26 parts of corundum powder, 10-12 parts of anti-seepage modified fiber, 0.3-0.5 parts of redispersible rubber powder, 2.8-3.0 parts of water reducer, 0.5-0.7 parts of water repellent, 4-6 parts of N-benzyl hexadecanoic acid amide and 2-4 parts of 4-iodophenylethynyltrimethylsilane are mixed uniformly to form a base mortar; Step B2, adding film-forming iron powder to the base mortar, using a mixer to mix all the components evenly, the stirring speed is 150-250 rpm, adding water during the stirring process, adjusting the consistency of the slurry to 45-55 mm, and obtaining a new type of anti-seepage mortar for backwater wall; The construction process of the new type of anti-seepage mortar for backwater wall comprises the following specific steps: Step C1, treating the wall surface to make it clean, free of oil stains and impurities, and setting magnets on the construction wall surface. The arrangement of the magnets is set according to the required membrane channel pattern; Step C2: Figure 1 As shown, mortar is applied and the mortar is evenly applied on the wall surface using a plastering tool. During the application process, the film-forming iron powder is attracted by a magnet to form a predetermined film channel. Among them, the coating thickness is 5-15mm; Step C3: After the application is completed, the mortar is cured to allow it to fully harden and form.

[0021] The following experiments were conducted on the new type of anti-seepage mortar for backwater wall: Experiment 1. The new type of anti-seepage mortar for backwater wall includes, by weight: 40 parts of silicate cement, 10 parts of fast-hardening sulphoaluminate cement, 280 parts of quartz sand, 22 parts of corundum powder, 10 parts of anti-seepage modified fiber, 0.3 parts of redispersible rubber powder, 2.8 parts of water reducer, 0.5 parts of water repellent, 4 parts of N-benzyl hexadecanoic acid amide, 2 parts of 4-iodophenylethynyltrimethylsilane, 15 parts of iron powder, 0.5 parts of retarder, and 2.5 parts of acrylic emulsion; Experiment 2. A new type of anti-seepage mortar for backwater wall, including, by weight: 50 parts of silicate cement, 15 parts of fast-hardening sulphoaluminate cement, 320 parts of quartz sand, 26 parts of corundum powder, 12 parts of anti-seepage modified fiber, 0.5 parts of redispersible rubber powder, 3.0 parts of water reducing agent, 0.7 parts of water repellent, 6 parts of N-benzyl hexadecanoic acid amide, 4 parts of 4-iodophenylethynyltrimethylsilane, 25 parts of iron powder, 1.5 parts of retarder, and 5 parts of acrylic emulsion; Experiment 3. A new type of anti-seepage mortar for back-water wall includes, by weight: 45 parts of silicate cement, 12.5 parts of fast-hardening sulphoaluminate cement, 300 parts of quartz sand, 24 parts of corundum powder, 11 parts of anti-seepage modified fiber, 0.4 parts of redispersible rubber powder, 2.9 parts of water reducer, 0.6 parts of water repellent, 5 parts of N-benzylhexadecanoic acid amide, 3 parts of 4-iodophenylethynyltrimethylsilane, 20 parts of iron powder, 1.0 part of retarder, and 3.5 parts of acrylic emulsion.

[0022] Performance Testing The new anti-seepage mortar for backwater wall prepared in Experiments 1 to 3 was poured into the mold, and standard curing was performed for 7 days. According to the JGJ / T70-2009 standard, the anti-seepage test was carried out using the SS-15 mortar anti-seepage instrument; the prismatic specimens with a specification of 40×40×160mm were cast, and standard curing was performed for 28 days. The flexural performance test was carried out using an electronic universal testing machine. The specific test data are shown in the following table: Test items Impermeability pressure / MPa Flexural strength / MPa Experiment 1 1.77 10.54 Experiment 2 1.91 11.35 Experiment 3 1.84 10.97 The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The iron powder and the acrylic emulsion are mixed evenly, so that the acrylic emulsion is evenly wrapped on the surface of the iron powder; as a film-forming component, the acrylic emulsion can form a stable film layer on the surface of the iron powder, which not only enhances the corrosion resistance of the iron powder, but also forms an additional anti-seepage barrier in the mortar. After adding the retarder, it is further ensured that the film-forming component forms a stable film layer on the surface of the iron powder. The function of the retarder is to delay the hydration reaction speed of the cement and prevent it from solidifying prematurely during the mixing process. After drying, the film-forming component is completely solidified on the surface of the iron powder to obtain a film-forming iron powder; As a ferromagnetic material, iron powder will be magnetized and generate magnetic moment in the magnetic field, so that it will be oriented under the action of the external magnetic field. The magnetic field generated by the magnet will attract the iron powder to move. Since the surface of the iron powder is coated with film-forming components, the film-forming substances on the iron powder will also form a path as the iron powder moves. By adjusting the magnetic field strength and direction of the magnet, the arrangement and orientation of the iron powder in the mortar can be controlled. The direction of the magnetic moment is consistent with the direction of the external magnetic field, which enables the iron powder particles to be oriented in the magnetic field. By setting magnets on the wall in advance and arranging them according to the desired membrane channel pattern, a magnetic field with a specific direction can be formed. When the mortar is applied, the film-forming iron powder in the mortar will be attracted by this magnetic field, so that it will move in a directional manner along the direction of the magnet arrangement to form a predetermined membrane channel. Through the attraction of the magnet, the film-forming material on the iron powder forms a predetermined membrane channel in the mortar. By forming a specific membrane channel, the new anti-seepage mortar for backwater walls can guide the infiltrated water to flow out along a predetermined path, avoiding the penetration and accumulation of water in the mortar; the directional guiding effect of the magnet enables the film-forming iron powder to accurately form the required membrane channel pattern during the application process, thereby improving the formation accuracy and aesthetics of the membrane channel; because the iron powder is directional arranged under the action of the magnetic field, the formed membrane channel is more stable and is not easily deformed or blocked by subsequent construction or external factors; by setting magnets and adjusting their arrangement, the formation position and shape of the membrane channel can be controlled, thereby simplifying the construction process; Due to the combined effect of the predetermined membrane channels and anti-seepage components formed in the mortar, the anti-seepage performance of the mortar is significantly improved, protecting the wall from moisture erosion and damage. The precise membrane channel formation improves the anti-seepage performance of the mortar, allowing moisture to be discharged more effectively through the membrane channel. Moisture flows out along the membrane channel, which is convenient for timely detection and maintenance; the simplified construction process and precise membrane channel formation reduce the complexity and time cost of manual operation and improve construction efficiency; the stable membrane channel structure promotes the hardening and strength improvement of the mortar. At the same time, the addition of iron powder also increases the density and skeleton support of the mortar, further enhancing the overall strength of the mortar.

[0023] Example 2: The above-mentioned Example 1 utilizes a magnet to perform magnetic field treatment and guidance on the film-forming iron powder. Based on the magnetization characteristics of ferromagnetic materials and the directional guiding effect of the magnetic field on the magnetized object, a membrane channel is formed to improve the anti-seepage performance of the mortar. In order to further improve the anti-seepage performance and construction performance of the mortar, further improvements are made on the basis of Example 1.

[0024] The new anti-seepage mortar for backwater wall further comprises 5-10 parts by weight of an inorganic salt plugging agent; Step C2: After the predetermined membrane channel is formed, 5-10 parts of inorganic salt plugging agent are injected into the mortar through the membrane channel, specifically: Step C3: After the application is completed, the mortar is initially cured, the magnet is removed, and the membrane channel formed by the iron powder remains open; Inject the inorganic salt plugging agent solution into the mortar through the membrane channel, so that the inorganic salt plugging agent solution fully penetrates into the small gaps and capillaries inside the mortar; Continue to maintain the mortar, so that the inorganic salt plugging agent can crystallize inside the mortar, plug the membrane channels and gaps, and form a dense anti-seepage layer. Maintain until the mortar is fully hardened and formed; Among them, the inorganic salt plugging agent is calcium chloride, and the concentration of calcium chloride solution is 5%-10%; the injection pressure is 0.2-0.5MPa, and the curing time is 7-14 days.

[0025] For this embodiment, an experiment was conducted on the basis of Experiment 3 in Example 1. The difference between the experiment of this embodiment and Experiment 3 is that, through the above-mentioned method, 7 parts of inorganic salt plugging agent are injected into the mortar through the membrane channel, wherein the inorganic salt plugging agent is calcium chloride, the concentration of the calcium chloride solution is 7%, and the injection pressure is 0.2-0.5MPa.

[0026] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The membrane channel provides a path for the injection of inorganic salt plugging agents. Under pressure, the inorganic salt plugging agent solution can penetrate into the small gaps and capillaries inside the mortar through the membrane channel. As the water evaporates or participates in the reaction, the inorganic salt crystallizes inside the mortar to form a dense plugging layer; the inorganic salt will undergo a hydrolysis reaction in water to generate corresponding hydration products, which can fill the small gaps and capillaries inside the mortar to form a dense anti-seepage layer; after the application is completed, the mortar is initially cured to slightly harden its surface, but the interior still maintains humidity, which is conducive to the penetration and crystallization of the inorganic salt. After removing the magnet, the membrane channel formed by the iron powder remains open, providing conditions for the injection of inorganic salts; the mortar is continued to be cured, so that the inorganic salt plugging agent crystallizes inside the mortar, plugging the membrane channels and gaps to form a dense anti-seepage layer; The penetration and crystallization of inorganic salts effectively solves the water seepage problem caused by small gaps and capillaries inside the mortar. The anti-seepage performance of the mortar has been significantly improved, which can effectively prevent the penetration, accumulation and leakage of water. The sealing layer formed after the crystallization of inorganic salts not only blocks the gaps and membrane channels, but also enhances the overall strength of the mortar. It has high strength and stability, can resist the penetration and erosion of water for a long time, improves the mechanical properties of the mortar such as compression and bending resistance, and extends the service life of the mortar. By using the directional guidance of the magnet on the iron powder, a predetermined membrane channel can be easily formed to control the membrane. The formation position and shape of the channel improve the flexibility and accuracy of construction. The internal gaps and capillary channels of the mortar can be sealed without additional construction steps or equipment, which simplifies the construction process and reduces construction costs. The injection process of inorganic salts has little effect on the construction performance of the mortar. Mortar maintenance can continue without additional waiting time, making the mortar easy to apply and maintain, improving construction efficiency and shortening the construction period. The injection and crystallization process of the inorganic salt sealant can optimize the internal structure of the mortar, improve its density and uniformity, thereby enhancing the mechanical properties and durability of the mortar.

[0027] Embodiment 3: In the above-mentioned embodiment 2, inorganic salt plugging agents are injected into the mortar through the membrane channel, and the hydration reaction and plugging effect of the inorganic salt are utilized to further improve the anti-seepage performance of the mortar and optimize the construction performance. In order to further improve the anti-seepage performance and construction performance of the mortar, further improvements are made on the basis of embodiment 2.

[0028] The inorganic salt plugging agent solution also includes three different concentration ranges of inorganic salts: low concentration of 1%-3%, medium concentration of 5%-8%, and high concentration of 10%-15%; The specific dosage ratio is: low-concentration inorganic salt accounts for 10%-20% of the total amount of plugging agent, medium-concentration inorganic salt accounts for 30%-40%, and high-concentration inorganic salt accounts for 40%-60%; In step C3, low-concentration, medium-concentration and high-concentration inorganic salt plugging agent solutions are injected in sequence according to the dosage ratio.

[0029] For this embodiment, an experiment was conducted on the basis of Example 2. The difference between the experiment of this embodiment and the experiment of Example 2 is that the inorganic salt plugging agent solution also includes three different concentration ranges of inorganic salts: low concentration of 1%-3%, medium concentration of 5%-8%, and high concentration of 10%-15%; among them, the low concentration of inorganic salt accounts for 15% of the total amount of the plugging agent, the medium concentration of inorganic salt accounts for 35%, and the high concentration of inorganic salt accounts for 50%.

[0030] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Inorganic salts will undergo hydration reaction when in contact with water to generate hydration products. These hydration products can fill the pores and capillaries in the mortar, thereby improving the density of the mortar. The speed and degree of hydration reaction of inorganic salt solutions of different concentrations are different. Low-concentration solutions have strong permeability and can quickly enter the interior of the mortar; medium-concentration solutions begin to form hydration products while penetrating; high-concentration solutions form a dense plugging layer; by introducing inorganic salt solutions of different concentrations, a concentration gradient can be formed. Low-concentration inorganic salt solutions first penetrate into the mortar, providing a penetration path for subsequent medium and high-concentration inorganic salt solutions. Medium-concentration inorganic salt solutions further block pores and enhance the density of the mortar. High-concentration inorganic salt solutions form a dense plugging layer, effectively preventing water penetration; by controlling the dosage ratio of inorganic salts of different concentrations, the performance of the plugging agent can be optimized. Low-concentration inorganic salts are used in a moderate amount to ensure permeability; medium-concentration inorganic salts are used in a large amount to enhance the plugging effect; high-concentration inorganic salts are used in the largest amount to form a dense plugging layer; The combination of multi-concentration inorganic salts can form a denser plugging layer, effectively preventing water penetration; the penetration and plugging effect of low-concentration and medium-concentration inorganic salts provides a good penetration path and plugging basis for high-concentration inorganic salts, making the entire plugging layer more uniform and dense, significantly improving the anti-seepage performance of the mortar; Inorganic salts of different concentrations have different permeability and plugging effects, and can adapt to different gaps and capillary conditions inside the mortar; the control of injection sequence and pressure ensures that the inorganic salt solution can fully penetrate into the mortar, improving the flexibility and accuracy of construction. The control of dosage ratio makes the use of plugging agents more economical and efficient. The plugging agent has good construction performance and is easy to inject and maintain; The hydration products of high-concentration inorganic salts can absorb and retain a certain amount of water, play a role in absorbing a small amount of water, and enhance the mortar's ability to regulate moisture. The hydration products of high-concentration inorganic salts absorb and release moisture, regulate the internal humidity of the mortar, reduce cracking and strength loss caused by drying, and enable the mortar to maintain a certain humidity in a dry environment, thereby improving its durability and performance.

[0031] Example 4: The above-mentioned Example 3 introduces inorganic salt plugging agents of different concentrations and combines them with specific dosage ratios. Based on the principles of inorganic salt hydrolysis reaction, concentration gradient and dosage ratio control, the anti-seepage performance and construction performance of the mortar are significantly improved, and the durability and performance of the mortar are enhanced. In order to further improve the anti-seepage performance and construction performance of the mortar, further improvements are made on the basis of Example 3.

[0032] After the inorganic salts are completely dried, epoxy resin is also injected into the pores on the mortar surface through the membrane channels; In step C3, after the inorganic salt is completely dried, epoxy resin is injected into the pores on the surface of the mortar through the membrane channel; Among them, the injection pressure of epoxy resin is 0.1-0.3MPa, and the amount of epoxy resin used is 5%-20% of the total amount of inorganic salt plugging agent.

[0033] For this embodiment, an experiment was conducted on the basis of Example 3. The difference between the experiment of this embodiment and the experiment of Example 3 is that in step C3, after the inorganic salt is completely dried, epoxy resin is injected into the pores on the surface of the mortar through the membrane channel; wherein, the injection pressure of the epoxy resin is 0.1-0.3MPa, and the amount of epoxy resin used is 15% of the total amount of the inorganic salt plugging agent.

[0034] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: Epoxy resin is a high-performance polymer material with excellent adhesion and wear resistance. After the inorganic salt is completely dried, the epoxy resin is injected into the pores on the mortar surface through the membrane channel, which can further block the pores on the mortar surface and enhance the anti-seepage performance of the mortar. After injection, the epoxy resin will penetrate into the pores on the mortar surface and form a tight bond with the inorganic salt plugging agent inside the mortar; as the epoxy resin solidifies, a dense polymer film will be formed, covering the mortar surface, effectively preventing the penetration of moisture and harmful substances; by injecting epoxy resin, the end blocking of the pores inside and on the surface of the mortar is achieved, ensuring the stability of the system substances inside the mortar; the polymer film formed after the epoxy resin is cured has good durability and chemical stability, and can protect the mortar from erosion by the external environment for a long time; Through the inorganic salt hydrolysis reaction and the penetration and curing of epoxy resin, the pores inside and on the surface of the mortar are completely blocked, which significantly improves the anti-seepage performance of the mortar. This improvement in anti-seepage performance significantly improves the waterproof treatment of the backwater wall, which can effectively prevent the penetration of moisture and harmful substances and protect the safety and stability of the wall structure. The polymer film formed after the epoxy resin is cured has good durability and chemical stability, and can protect the mortar from the erosion of the external environment for a long time. Through the inorganic salt hydrolysis reaction and the sealing effect of the epoxy resin, the internal structure of the mortar is effectively reinforced and stabilized, and the mechanical properties of the mortar such as compressive strength and flexural strength are improved. This improvement in durability and performance can extend the service life of the mortar and reduce maintenance costs; The adhesion and sealing properties of epoxy resin not only improve the anti-seepage performance of the mortar, but also enhance its strength and stability; epoxy resin interacts with inorganic salt sealants, cement and other components in the mortar to form a tighter and stronger structural system, thereby improving the overall performance of the mortar.

[0035] Performance Testing The new type of anti-seepage mortar for backwater wall prepared in Example 2 to Example 4 was poured into a mold, standardly cured for 7 days, and the anti-seepage test was carried out using the SS-15 mortar anti-seepage instrument according to the JGJ / T70-2009 standard; a prismatic specimen with a specification of 40×40×160 mm was poured, standardly cured for 28 days, and the flexural performance test was carried out using an electronic universal testing machine. The specific test data are shown in the following table: Test items Impermeability pressure / MPa Flexural strength / MPa Example 1 (Experiment 3) 1.84 10.97 Embodiment 2 1.98 11.01 Embodiment 3 2.17 11.37 Embodiment 4 2.36 11.86 The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A new type of anti-seepage mortar for backwater wall, characterized in that: The composition includes, by weight: 40-50 parts of silicate cement, 10-15 parts of rapid hardening sulphoaluminate cement, 280-320 parts of quartz sand, 22-26 parts of corundum powder, 10-12 parts of anti-seepage modified fiber, 0.3-0.5 parts of redispersible rubber powder, 2.8-3.0 parts of water reducing agent, 0.5-0.7 parts of water repellent, 4-6 parts of N-benzyl hexadecanoic acid amide, 2-4 parts of 4-iodophenylethynyltrimethylsilane, 15-25 parts of iron powder, 0.5-1.5 parts of retarder, and 2.5-5 parts of acrylic emulsion. The iron powder is pretreated, and the specific steps are: Step A1, 15-25 parts by weight of iron powder and 2.5-5 parts of acrylic emulsion are mixed uniformly in a blender at a stirring speed of 60-100 rpm for 5-10 minutes, so that the acrylic emulsion is uniformly coated on the surface of the iron powder; Step A2, adding 0.5-1.5 parts of retarder to the mixed iron powder and acrylic emulsion and mixing evenly to form an iron powder mixture; Step A3: Place the treated iron powder mixture in a drying oven, control the temperature at 40-60°C, and dry for 2-4 hours to ensure that the film-forming components form a stable film layer on the surface of the iron powder to obtain film-forming iron powder.

2. The new anti-seepage mortar for backwater wall according to claim 1, characterized in that: The preparation of the new type of anti-seepage mortar for backwater wall comprises the following specific steps: Step B1, 40-50 parts of silicate cement, 10-15 parts of rapid hardening sulphoaluminate cement, 280-320 parts of quartz sand, 22-26 parts of corundum powder, 10-12 parts of anti-seepage modified fiber, 0.3-0.5 parts of redispersible rubber powder, 2.8-3.0 parts of water reducer, 0.5-0.7 parts of water repellent, 4-6 parts of N-benzyl hexadecanoic acid amide and 2-4 parts of 4-iodophenylethynyltrimethylsilane are mixed uniformly to form a base mortar; Step B2: Add film-forming iron powder to the base mortar, use a mixer to mix all components evenly at a stirring speed of 150-250 rpm, add water during the stirring process, and adjust the consistency of the slurry to 45-55 mm to obtain a new type of anti-seepage mortar for back-water wall.

3. The novel anti-seepage mortar for backwater wall according to claim 1, characterized in that: The new type of anti-seepage mortar for backwater walls further comprises 5-10 parts by weight of an inorganic salt plugging agent; the inorganic salt plugging agent is calcium chloride, and the concentration of the calcium chloride solution is 5%-10%.

4. The novel anti-seepage mortar for backwater wall according to claim 3, characterized in that: The inorganic salt plugging agent solution also includes three different concentration ranges of inorganic salts: a low concentration of 1%-3%, a medium concentration of 5%-8%, and a high concentration of 10%-15%.

5. The novel anti-seepage mortar for backwater wall according to claim 4, characterized in that: The usage ratio of the inorganic salts in different concentration ranges is: low concentration inorganic salts account for 10%-20% of the total amount of the plugging agent, medium concentration inorganic salts account for 30%-40% of the total amount of the plugging agent, and high concentration inorganic salts account for 40%-60% of the total amount of the plugging agent.

6. The novel anti-seepage mortar for backwater wall according to claim 5, characterized in that: The new type of anti-seepage mortar for backwater wall also includes epoxy resin; the amount of epoxy resin used is 5%-20% of the total amount of inorganic salt plugging agent.

7. A construction process for the new type of anti-seepage mortar for backwater wall according to any one of claims 1 to 6, characterized in that: The specific steps are: Step C1, treating the wall surface to make it clean, free of oil stains and impurities, and setting magnets on the construction wall surface. The arrangement of the magnets is set according to the required membrane channel pattern; Step C2, applying mortar, using a plastering tool to evenly apply the mortar on the wall surface, the film-forming iron powder is attracted by the magnet during the application process to form a predetermined membrane channel; Step C3: After the application is completed, the mortar is cured to allow it to fully harden and form.

8. The construction process of the new type of anti-seepage mortar for backwater wall according to claim 7, characterized in that: After the predetermined membrane channel is formed in step C2, 5-10 parts of inorganic salt plugging agent are injected into the mortar through the membrane channel, specifically: Step C3: After the application is completed, the mortar is initially cured, the magnet is removed, and the membrane channel remains open; Inject inorganic salt plugging agent solution into the mortar through the membrane channel, with an injection pressure of 0.2-0.5MPa; Continue to cure the mortar to allow the inorganic salt plugging agent to crystallize inside the mortar, plugging the membrane channels and gaps to form a dense anti-seepage layer, and cure until the mortar is fully hardened and formed.

9. The construction process of the new type of anti-seepage mortar for backwater wall according to claim 8, characterized in that: In step C3, low-concentration, medium-concentration and high-concentration inorganic salt plugging agent solutions are injected in sequence according to the dosage ratio.

10. The construction process of the new type of anti-seepage mortar for backwater wall according to claim 9, characterized in that: In step C3, after the inorganic salt is completely dried, epoxy resin is injected into the pores on the surface of the mortar through the membrane channel; the injection pressure of the epoxy resin is 0.1-0.3 MPa.

Citation Information

Patent Citations

  • Interface mortar for anticorrosive paint and preparation method thereof

    CN117303836A

  • Preparation method of high-impermeability concrete

    CN110482941A

  • Lightweight plastering mortar and preparation method thereof

    CN115745537A